Nitrogen addition alters arbuscular mycorrhizal fungi and soil bacteria networks without promoting phosphorus mineralization in a semiarid grassland - Jian-Xia Yang; Yang Peng; Jun-Jie Yang; Yun-Hai Zhang; Qiang Dong; Qiu-Shi Li; Xing-Guo Han; Cheng Gao (Communications Biology)
Abstract Mycorrhiza interplays with the microbiome in adaptation to environmental fluctuation, yet how arbuscular mycorrhizal fungi (AMF) and the associated microbiome respond to nitrogen addition remains poorly understood. Here, we addressed this gap by conducting amplicon sequencing of AMF 18S rRNA and bacterial 16S rRNA operons, along with shotgun metagenome sequencing, using soil samples collected from a semiarid grassland that has received nitrogen inputs for 11 years at different levels. We found that the nitrogen response of the AMF community was characterized by a negative association whereby increasing nitrogen addition leads to higher beta diversity and lower alpha diversity. Multiple co-inertia analyses revealed a coordinated response of the AMF community, bacterial community, and bacterial functions to nitrogen addition, which as a whole was strongly related to soil phosphorus availability. Besides, through network analysis of AMF with bacteria and bacterial functional genes, we found that nitrogen addition selected Actinobacteria and enriched functions of transporters, amino acid synthesis and metabolism, and replication repair, whereas there was no evidence for the enrichment of phosphorus mineralization functions.